Molecular genetics to inform spatial management in benthic invertebrate fisheries: a case study using the Australian Greenlip Abalone - K. J. Miller; C. N. Mundy; S. Mayfield (Molecular Ecology, 2014)
Hierarchical sampling and subsequent microsatellite genotyping of >2300 H aliotis laevigata (greenlip abalone) from 19 locations distributed across five biogeographic regions have substantially advanced our knowledge of population structure and connectivity in this commercially important species. The study has found key differences in stock structure of H . laevigata compared with the sympatric and congeneric H aliotis rubra (blacklip abalone) and yielded valuable insights into the management of fisheries targeting species characterized by spatial structure at small scales (i.e. S‐fisheries). As with H. rubra, H. laevigata comprise a series of metapopulations with strong self‐recruitment. However, the spatial extent of H. laevigata metapopulations (reefal areas around 30 km 2 ; distances of up to 135 km are effective barriers to larval dispersal) was substantially greater than that identified for H. rubra (Miller et al . 2009). Differences in the dynamics and scale of population processes, even between congeneric haliotids as made evident in this study, imply that for S‐fisheries, it is difficult to generalize about the potential consequences of life history commonalities. Consequently, species‐specific management reflective of the population structure of the target species remains particularly important. This will likely require integration of information about stock structure and connectivity with data on life history and population dynamics to determine the necessary input (e.g. number of fishers, fishing effort) and output (e.g. minimum legal size, total allowable catch) controls to underpin their sustainable management.